Impact of Structural Reformson Productivity Growth in Industrial Countries - Salgado, Ranil (IMF Working Papers; Working Paper ;, 2002)
This paper investigates the impact of structural reforms on productivity growth. A panel analysis of 20 OECD countries finds that the impact of structural reforms on productivity growth may be weak or negative in the short run, possibly due to adjustment costs and the need for firms to learn how to operate in a less regulated and more competitive environment. In the long run, however, structural reforms are found to have significantly positive effects on productivity growth.